Learning to Labour in China. (December 2018) - Moskowitz, Scott; She, Xi; Xiong, Chunwen
This article offers analysis of the Chinese reception and adoption of Paul Willis's landmark book, Learning to Labour . Specifically, we recount the early introduction and translation of the book to Chinese readers and catalogue the ways in which Learning to Labour has been fruitfully applied in China, while highlighting some shortcomings in terms of the generalized Chinese interpretation of the text in translation. Despite these potential shortcomings and gaps in translation, we note the influence of Learning to Labour and its author Paul Willis on the growing interest in and commitment to ethnographic work in China and discuss its potential for increased application and relevance moving forward.